Changes in serum interleukin-6 (IL-6) and C-reactive protein (CRP), PCT after Early Resuscitation in Patients with Severe Acute Pancreatitis: Changes in serum interleukin-6 (IL-6) and C-reactive protein (CRP), PCT - Wang, Jinlong (Journal of Medical Biochemistry, 2025)
Aim: this work investigated the effects of different early resuscitation fluid replenishment rates (FRRs) on inflammation (serum interleukin-6 (IL-6) and C-reactive protein (CRP), PCT ) and complications in patients with severe acute pancreatitis (SAP). Methods: Sixty-six patients with SAP were studied. According to the ratio of total fluid replenishment 24 h after admission to that 72 h (FRR), the patients were rolled into a low FRR group (Low group), a moderate FRR group (Moderate group), and a high FRR group (High group), with 22 cases in each. Serum related indexes, APACHE Ⅱ score, HCT, systemic inflammatory response syndrome (SIRS) duration, length of hospital stay (LOS), and complication rate (CR) were determined and compared. Results: The results suggested that ALT, AST, SCr, BUN, TBil, APACHE Ⅱ, scores and HCT in the Moderate group were the lowest (P<0.05), while those in the High group were the highest (P<0.05). After the patients were treated for 72 h, the IL-6, CRP, and PCT in the Low group and the High group were higher than those in the Moderate group, exhibiting differences with P<0.05 and P<0.01, respectively. The SIRS duration and LOS in the Low and High groups were longer and presented differences with P<0.05 and P<0.01 to the Moderate group, respectively. The rates of MODS, mechanical ventilation, pancreatic necrosis infection, and death in the Moderate group were the lowest (P<0.05). conclusion the moderate FRR could effectively alleviate the inflammatory response of patients with SAP, shorten the treatment time, and reduce the CR